Renal Lymphatics: Anatomy, Physiology, and Clinical Implications - Russell, Peter Spencer; Hong, Jiwon; Windsor, John Albert; Itkin, Maxim; Phillips, Anthony Ronald John (Frontiers in Physiology, 2019)
Renal lymphatics are abundant in the cortex of the normal kidney but have been largely neglected in discussions around renal diseases. They originate in the substance of the renal lobule as blind-ended initial capillaries, and can either follow the main arteries and veins towards the hilum, or penetrate the capsule to join capsular lymphatics. There are no valves present in interlobular lymphatics, which allows lymph formed in the cortex to exit the kidney in either direction. There are very few lymphatics present in the medulla. Lymph is formed from interstitial fluid in the cortex, and is largely composed of capillary filtrate, but also contains fluid reabsorbed from the tubules. The two main factors that contribute to renal lymph formation are interstitial fluid volume and intra-renal venous pressure. Renal lymphatic dysfunction, defined as a failure of renal lymphatics to adequately drain interstitial fluid, can occur by several mechanisms. Renal lymphatic inflow may be overwhelmed in the setting of raised venous pressure (e.g. cardiac failure) or increased capillary permeability (e.g. systemic inflammatory response syndrome). Similarly, renal lymphatic outflow, at the level of the terminal thoracic duct, may be impaired by raised central venous pressures. Renal lymphatic dysfunction, from any cause, results in renal interstitial edema. Beyond a certain point of edema, intra-renal collecting lymphatics may collapse, further impairing lymphatic drainage. Additionally, in an edematous, tense kidney, lymphatic vessels exiting the kidney via the capsule may become blocked at the exit point. The reciprocal negative influences between renal lymphatic dysfunction and renal interstitial edema are expected to decrease renal function due to pressure changes within the encapsulated kidney, and this mechanism may be important in several common renal conditions.